Informalidade e subdesenvolvimento: os entraves do mercado de trabalho brasileiro para o desenvolvimento econômico no século XXI - Cardoso, Luiz Henrique Santos (2023)
The informality historically present in underdeveloped countries like Brazil has been largely characterized by marginalized workers without access to labor rights guaranteed by law and productive units with low productivity and organization. Throughout the decades during the 20th century, this scenario was consolidated in different ways, deepening its most precarious aspects to the workforce, relating to the heterogeneous structures present in underdeveloped economies. In this way, through a critical reading of ECLAC's structuralist theorists, fundamentally based on Raul Prebisch and Celso Furtado, we seek to analyze the historical formation of the Brazilian labor market and its correlation with the dynamics of underdevelopment. We emphasize that the view of the ECLAC structuralists on Brazilian underdevelopment undertakes a fundamental understanding of the labor market, in the same way that the Marxist view of Chico de Oliveira contributes by complementing in a critical way the structuralist views on informality and its operating logic subordinated to capital, in such a way that the condition of an underdeveloped country persists in the 21st century. From this, we observe that informality has an intrinsic complexity for its conceptualization, measurement, and quantification, making it difficult to design public policies to combat it